Social Physique Anxiety, Physical Self-Perceptions and Eating Disorder Risk: A Two-Sample Study. - Sharon R. Bratrud; Marissa M. Parmer; James R. Whitehead1; Robert C. Eklund (Pamukkale University, 2010)
We analyzed data from two independent samples to assess the predictive relationships between eating disorder risk (RISK) and physical self-esteem and social physique anxiety. Female college athletes completed the Physical Self-Perception Profile (PSPP), the Social Physique Anxiety Scale (SPAS), and the Drive For Thinness (THIN), Bulimia (BUL), and Body Dissatisfaction (BDIS) subscales of the Eating Disorder Inventory. They also completed socially desirability (SD) scales. Our analyses assessed the unique contribution of BDIS to risk prediction (THIN and BUL) after SD, SPAS and PSPP had been statistically controlled for. The associations between variables, and the predictive contributions of PSPP, SPAS, and BDIS to eating disorder risk as measured by THIN were similar in both studies. However, we found dissimilar results with regard to prediction of BUL. The R2 shrinkage between studies suggests satisfactory cross validation with respect to predicting THIN, but not for the prediction of BUL. No scales were unduly prone to distortion by SD responding. These data support the hypothesis that PSPP and SPAS may contribute to predicting aspects of eating disorder risk, and further study of the contributions of PSPP and SPAS to eating disorder risk seems to be warranted.